Challenges in Cultivating Knowledge in University-Industry-Government Partnerships — Qatar as a Case Study - Abduljawad, Haytham (The Muslim world, 2015)
In 2008, the state of Qatar articulated a national vision to transform its hydrocarbon-based economy to a knowledge based economy (KBE) by the year 2030. A KBE derives its value from intangible assets (knowledge) where production, distribution, and utilization of such assets are the main drivers for economic growth and wealth generation. Knowledge assets are created through various intra and inter organization processes. University-Industry-Government (UIG) collaborations are major contributors to knowledge assets at organizational and national levels. UIG partnership is a fairly new concept and a complex process that has not been formally implemented, supported, or monitored in the state of Qatar. To explore the UIG partnership, and to assess the effectiveness of knowledge creation and exchange, a single case study method was used to capture and reveal perspectives of participants involved in the partnership. Based on perspectives from 31 participants from (a) Qatar University, (b) Oil and Gas industry organizations and (c) government and semi government institutions in the state of Qatar, organizations are indeed taking initial steps to stimulate and deepen university-industry partnerships. This paper identifies challenges in cultivating the knowledge created and transferred from UIG partnerships and recommends key solutions to the challenges organizations are faced with in efforts to institutionalize the knowledge that is produced from collaborations with academia.